A table in the presence : the dramatic account of how a U.S. Marine battalion experienced God's presence amidst the chaos of the war in Iraq - Cash, Carey H, Lt. (S.l. : Thomas Nelson, 2004)
On April 10th, 2003, the 1st Battalion, 5th Marine Regiment, faced with the task of seizing the presidential palace in downtown Baghdad, ran headlong into what Lieutenant Colonel Oliver North called, "the worst day of fighting for U.S. Marines." Hiding in buildings and mosques, wearing civilian clothes, and spread out for over a mile, Saddam Hussein's militants rained down bullets and rocket propelled grenades on the 1st Battalion. But when the smoke of the eight-hour battle cleared, only one Marine had lost his life. Some said the 1st Battalion was incredibly lucky. But in the hearts and minds of the Marines who were there, there was no question. God had brought them miraculously through that battle. As the 1st Battalion's chaplain, Lieutenant Carey Cash had the unique privilege of seeing firsthand, from the beginning of the war to the end, how God miraculously delivered, and even transformed, the lives of the men of the 1st Battalion.
Paperback.
Keywords: Biography/Autobiography.; Military -- Other; Biography & Autobiography -- Military; Military -- Iraq War (2003.); Religious; Military -- Iraq War; Military; Biography -- Autobiography; History; Military -- United States